Building Athlete Entrepreneurship and Social Capital: A Case Study on Sport Fund Athletes - Aaltonen, Amanda (2025)
This master’s thesis investigates the rising phenomenon of athlete entrepreneurship in Finland within a case study setting of athletes in individual disciplines. The studied athletes are participating in an innovative program by Sport Fund Management Ltd, which offers early-stage funding and social support structures for athlete entrepreneurs. The research data consists of six athletes’ interviews.